Giant Posttraumatic Angiolipoma of the Forearm: A Case Report and Review of the Literature - Athanasios Fotiadis; Petros Ioannidis; Ioannis Skandalos; Stergios Papastergiou; Aristeidis Vrettakos; Theodoros Tzigkalidis; Themistoklis Vampertzis (Case Reports in Orthopedics)
Angiolipoma is a type of lipoma, a benign soft tissue tumor. It is distinguished by the excessive degree of vascular proliferation and the presence of mature adipocytes. It occurs commonly on the trunk and extremities. Angiolipomas larger than 4 cm are classified as “giant,” and due to their size, histological evaluation is necessary to exclude malignancy. We report a case of a male patient who suffered from a giant noninfiltrating intramuscular angiolipoma which formed after venipuncture in the antecubital fossa. Clinical examination showed a palpable painless soft mass. Computed tomography (CT) and magnetic resonance imaging (MRI) demonstrated a giant angiolipoma on the right forearm. Surgical removal of the mass was performed, and the biopsy was negative for malignancy. To the best of our knowledge, this is the first report in the literature of posttraumatic intramuscular angiolipoma. Physicians and orthopedic/general surgeons should be aware of the possibility of soft tissue masses in a posttrauma situation.